Level of Preparation of General Education Teachers to Include Students with Autism Spectrum Disorders - Emily E. Teffs; Kathleen M. Whitbread (Arizona State University, 2009)
Since 1998 there has been a dramatic increase in children diagnosed with Autism Spectrum Disorders (ASD) resulting in an estimated prevalence of 1 in 150 children. Federal law requires schools to educate children with ASD in the least restrictive environment, increasing the number of children with ASD in regular classrooms. Teacher preparation rarely includes training in ASD, leaving many teachers unprepared to accommodate these students. Using an online survey distributed to a random sample of Connecticut teachers, this study explored formal and informal preparation for teachers as well as teachersâ feelings of confidence and competence to teach children with ASD.